Phase II Trial of Sorafenib in Patients with Chemotherapy Refractory Metastatic Esophageal and Gastroesophageal (GE) Junction Cancer. - Yelena Y Janjigian; Efsevia Vakiani; Geoffrey Y Ku; Jessica M Herrera; Laura H Tang; Nancy Bouvier; Agnès Viale; Nicholas D Socci; Marinela Capanu; Michael Berger; David H Ilson (PLoS ONE, 2015)
Purpose Vascular endothelial growth factor receptor (VEGFR2) directed therapies result in a modest survival benefit for patients with advanced esophageal and gastroesophageal (GE) junction cancer. Platelet-derived growth factor receptor (PDGFR) may contribute to escape from VEGFR2 inhibition. We evaluated the efficacy of sorafenib, a broad spectrum tyrosine kinase inhibitor targeting VEGFR2 and PDGFR as well as RET and RAF1, in patients with metastatic chemotherapy refractory esophageal and GE junction cancer. Patients and methods This phase II trial of sorafenib 400 mg twice daily enrolled chemotherapy refractory patients with metastatic esophageal and GE junction cancer with primary endpoint of progression-free survival (PFS) rate at two months. Secondary endpoints included overall survival, objective response rate and toxicity. Results Among 34 patients, 8 week Kaplan-Meier estimated PFS was 61% (90%CI 45 to 73%). Median PFS is 3.6 months (95% CI 1.8 to 3.9 months), with median overall survival OS 9.7 months (95% CI 5.9 to 11.6 months). Grade 3 toxicities were uncommon and included hand foot skin reaction, rash, dehydration and fatigue. One patient (3%) with ongoing complete response and remains on trial for over 5 years. Whole exome sequencing of this tumor revealed mutations in many cancer-associated genes including ARID1A, PIK3CA, and TP53, and focal amplifications of HMGA2 and MET. Conclusion Sorafenib therapy results in disease stabilization and encouraging PFS in patients with refractory esophageal and GE junction cancer. Trial registration ClinicalTrials.gov NCT00917462.